Effects of bacitracin zinc, potassium diformate and lauric acid on duodenal digestive functions, intestinal morphology and caecal microflora of broilers - Ying Lin; Shi-Zhong Hu; Yang Sun; Ling Jin; Chang-Kang Wang; Yu-Yun Gao (Czech Journal of Animal Science, 2022)
This study investigated the effects of bacitracin zinc, potassium diformate and lauric acid on duodenal digestive functions, intestinal morphology and caecal microflora of broilers. A total of 240 male broilers were randomly allotted to four treatments consisting of five replicates with 12 birds per replicate. The dietary treatments were CON group (basal diet), ANT group (basal diet + 40 mg/kg bacitracin zinc), KDF group (basal diet + 1 000 mg/kg potassium diformate), and LA group (basal diet + 500 mg/kg lauric acid). The results showed that the chymotrypsin activity was significantly enhanced on days 21 and 42 in KDF group compared with CON group (P < 0.05), but there were no effects on the activities of trypsin and amylase (P > 0.05). No differences in digestive enzyme activities were found between ANT and LA groups (P > 0.05). Compared with CON group, the villus length and the villus-to-crypt ratio were significantly increased on days 21 and 42, and the crypt depth was significantly decreased in ANT, KDF and LA groups (P < 0.05). Compared with CON group, the supplementation of LA increased the relative abundance of Faecalibacterium on day 21 and the relative abundance of Bacillus on day 42 in caecum, while the supplementation of KDF increased the relative abundance of Faecalibacterium and decreased the relative abundance of Dorea on day 42 in caecum (P < 0.05). In conclusion, the supplementation of KDF enhanced the chymotrypsin activity. Dietary KDF and LA maintained the intestinal morphology by improving the villus length and the villus-to-crypt ratio and decreasing the crypt depth, and regulated the caecal microflora.